EKRANISASI NOVEL DALAM BENTUK FILM REMBULAN TENGGELAM DI WAJAHMU KARYA TERE-LIYE DAN DANIAL RIFKI - Aang Fatihul Islam (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2022)
Abstract The emergence of the phenomenon of adapting novels into films is a change in the substance of the discourse that gave rise to the term ecranization. This study aims to describe the process of ecranization of Rembulan Tenggelam di Wajahmu from a novel into a film. This research is descriptive qualitative. The data of this research are in the form of shrinking in novels and films, additions in novels, and various changes in novels and films in which there is a process of ecranization of Rembulan Tenggelam di Wajahmu from the novel into the film. The source of the data for this research is the novel Rembulan Tenggelam di Wajahmu by Tere-liye, published in 2001. The film Rembulan by Danial Rifki was produced by Max Pictures, in 2019, with a duration of 92 minutes. Data collection was carried out by two procedures, namely observation and documentation. The results of this study indicate that the process of ecranization of Rembulan Tenggelam di Wajahmu from a novel into a film occurs in three elements, namely elements of plot, character, and setting, namely due to shrinking, adding, and varying changes. Meanwhile, the shrinkage of plot, characters, and setting occurs because the media used in making the novel into a film has a different shape. Overall, it can be seen that the reduction in visualization from novels to films is still reasonable to do. This is because the omission of stories, characters, and settings is taken in parts that are not so important to visualize. The addition of the plot, characters, and setting in the film as a whole is still relevant to the story in the novel, it's just that the visualization in the form of a film is made more interesting by the many story conflicts, additional characters and backgrounds that appear so that the story in the film is more alive than the original. stories in novels. This appearance is to add to the essence of the film in the context of visualization so that it can easily bring the audience into the storyline. As for the changes in the various plots, characters, and settings made in the visualization to the form of the film as a whole, it is not far from the depiction in the novel.